Quaternary Ammonium Silica Nanoparticles for Antimicrobial Implantable Medical Devices: An In Vitro Study - Eitam Weiss; Ariel Berl; Ofir Shir-az; Biader Samih Bilal; Ervin I. Weiss; Yossi Paitan; Natan Zaltsman; Alexander Golberg; Avshalom Shalom (Life)
Biofilm formation on prostheses and implanted devices can lead to serious complications and increased healthcare expenditures. Once formed, biofilm management is difficult and may involve a long course of antibiotics, additional surgery, and, occasionally, implant removal. This study evaluated the antibacterial properties of medical-grade silicone samples integrated with novel, non-leaching, antibacterial, quaternary ammonium silica (QASi) particles. Our collaborators (Nobio, Israel) prepared silicone sheets integrated with antibacterial QASi nanoparticles. Samples containing 0.5%, 0.75%, and 1%, QASi particles were evaluated for antibacterial properties against S. epidermidis, S. aureus, methicillin-resistant S. aureus (MRSA), E. faecalis, and P. aeruginosa using the direct contact test. The tested silicone samples integrated with QASi particles showed no bacterial growth, while growth was observed in control silicone samples without QASi. In addition, the agar diffusion test, used to evaluate the leaching of antibacterial components, exhibited no inhibition zone around the samples indicating that the QASi particles do not leach into surrounding milieu. The QASi nanoparticles exhibited very potent antibacterial surface properties, killing all viable bacteria placed on their surface. Incorporating QASi nanoparticle technology into medical products during production has the potential to create an antimicrobial surface that prevents microbial colonization and biofilm formation.